Notes on Two Deep-Water Calanoids (Aetideopsis rostrata and Neoscolecithrix farrani) from Lancaster Sound - Shih, Chang-Tai; Stallard, Nell (ARCTIC, 1982)
Two unusual calanoid copepods were collected in deep-water samples from eastern Lancaster Sound. The hitherto unknown male of Aetideopsis rostrata is described and the first record of Neoscolecithrix farrani from the western North Atlantic is reported.Key words: Canadian Arctic, zooplankton, Calanoida, morphology, distribution